2009
DOI: 10.1002/gps.2353
|View full text |Cite
|
Sign up to set email alerts
|

Cerebrospinal fluid total tau as a marker of Alzheimer's disease intensity

Abstract: These findings support the hypothesis that increased levels of T-tau reflect the intensity of the disease and are associated with a more rapid disease progress.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
71
0
2

Year Published

2010
2010
2022
2022

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 114 publications
(82 citation statements)
references
References 46 publications
(43 reference statements)
6
71
0
2
Order By: Relevance
“…First, the ventricular CSF tau in this study was lower than spinal CSF tau measured from live patients (33)(34)(35). This difference might be attributable to different ELISA kits, heterogeneous patient populations or anatomic sources of CSF.…”
Section: à6mentioning
confidence: 64%
“…First, the ventricular CSF tau in this study was lower than spinal CSF tau measured from live patients (33)(34)(35). This difference might be attributable to different ELISA kits, heterogeneous patient populations or anatomic sources of CSF.…”
Section: à6mentioning
confidence: 64%
“…The degree of increase in CSF T-tau in chronic neurodegenerative disorders is highest in disorders with the most rapid neuronal degeneration, such as Creutzfeldt-Jakob disease (Otto et al 1997). High CSF T-tau is also associated with a faster progression from mild cognitive impairment (MCI) to AD (Blom et al 2009), and a more rapid cognitive decline and higher mortality in AD cases (Samgard et al 2009;Wallin et al 2009). However, one study found that CSF Ttau correlates with postmortem tangle load (Tapiola et al 2009), suggesting that the release of tau specifically from degenerating tanglebearing neurons may contribute to the CSF level of T-tau.…”
Section: Fluid Biomarkers and The Brainmentioning
confidence: 99%
“…Positive correlations between CSF levels of P-tau 181 and P-tau 231 (tau phosphorylated at residues 181 and 231, respectively) and neocortical tangle pathology at autopsy have been reported (Buerger et al 2006;Tapiola et al 2009). High CSF P-tau181 is also associated with a faster progression from MCI to AD (Blom et al 2009), and a more rapid cognitive decline in AD cases (Samgard et al 2009), as well as those with very mild AD dementia (Snider et al 2009). These findings support the hypothesis that the CSF level of P-tau reflects the phosphorylation state of tau and the formation of tangles in the brain.…”
Section: Fluid Biomarkers and The Brainmentioning
confidence: 99%
“…Its levels increase in Creutzfeld-Jakob disease, and it may also be found in dementia associated with VCI, cerebral trauma and AD [157][158][159]. The usefulness of tau protein in the diagnosis of vascular dementia is to exclude other etiologies, so that there are no cut-off points for the diagnosis of vascular pathology [160].…”
Section: Genetic and Inflammatory Biomarkers And Their Neuropathologimentioning
confidence: 99%
“…There is usually an elevation of this ratio in patients with vascular dementia (particularly due to subcortical vessel disease) [156,159,164].…”
Section: Csf and Serum Albumin Concentration Indexmentioning
confidence: 99%